Penderitaan Tokoh Perempuan dalam Novel Romansa 2 Benua Karya Pipiet Senja - Mahfira, Hannifia Dalia Azza; Fauzan, Akhmad (CV. Eduartpia Publisher, 2024)
This research is motivated by the prevalence of violence against women, which is a significant factor contributing to their suffering. The purpose of this study is to describe the various forms of suffering experienced by female characters in the novel